Bahasa Inggris - Aprilia, Aniza; Pratomo, Hafidz Triantoro Aji; Nugroho, Setyadi (jitek, 2025)
Children with Down's syndrome have delays in language development, particularly in vocabulary acquisition. Home-based programs offered by parents play an important role in improving the vocabulary of children with Down syndrome. The aim of this study was to analyze the effect of home programs on the vocabulary development of children with Down syndrome. This study used a quantitative method with a “quasi-experimental” non-equivalent control group design. The sample was divided into two groups: the intervention group, which received the home program, and the control group, which did not receive the treatment. Data were analyzed using a paired t-test and an independent t-test. The results of the analysis showed that there was a significant difference between the intervention group and the control group. The results of the paired T-test in the intervention group showed a p-value = 0.016, while in the control group p = 0.080. The independent T-test showed a p-value = 0.005 (p < 0.05), demonstrating a significant effect of the home program on vocabulary improvement in children with Down's syndrome. In conclusion, the more parents are involved in the home program proposed by the speech therapist, the more Down syndrome children improve their vocabulary.